2019
DOI: 10.3892/mmr.2019.10622
|View full text |Cite|
|
Sign up to set email alerts
|

Filamin A regulates EGFR/ERK/Akt signaling and�affects colorectal cancer cell growth and migration

Abstract: The metastasis and recurrence rate, and the overall prognosis of colorectal cancer (CRC) remain unsatisfactory. Filamin A (FLNa), as an actin-binding protein, can interact with various signaling molecules and membrane receptors to affect cell signal transduction and function. However, whether FLNa is involved in the progression of CRC remains to be elucidated. The aim of the present study was to explore the role of FLNa in CRC cell proliferation and migration, as well as in the regulation of epidermal growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Numerous studies revealed the positive role of ERK pathway in progression of CRC. The aberrant activation of ERK1/2 facilitated the proliferation and immigration of CRC cells and also promoted the metastasis [22][23][24][25][26]. Meanwhile, ERK pathway was well known to regulate the osteoclastogenesis, many signals can enhance the osteoclast formation through activation of ERK pathway [27][28][29][30][31], but downstream of ERK in regulating osteoclastogenic induction was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies revealed the positive role of ERK pathway in progression of CRC. The aberrant activation of ERK1/2 facilitated the proliferation and immigration of CRC cells and also promoted the metastasis [22][23][24][25][26]. Meanwhile, ERK pathway was well known to regulate the osteoclastogenesis, many signals can enhance the osteoclast formation through activation of ERK pathway [27][28][29][30][31], but downstream of ERK in regulating osteoclastogenic induction was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The module itself has the best match with the MAPK signaling pathway. Further support of the DriveWays' choice of FLNA as a candidate driver is found in various recent studies demonstrating its role in tumor progression in a wide range of cancer types [51][52][53] . Repeating the same analysis under the breast cancer setting we find that PIK3R1, CDK4, CDK6, and SF3B1 satisfy the criteria for driver candidacy, that is each one appears among the top twenty DriveWays modules, does not exist in the reference gene set CMbreast, but does exist in the KEGG pathway corresponding to the best match of its module.…”
Section: Definitions Of Quality Measures For Evaluations Based On Modmentioning
confidence: 83%
“…PrP C has been discovered to be present in a Pro-PrP form, neither having the GPI anchor nor being glycosylated in different human cancer cell lines and tissues [46,48,49]. Interestingly, the Pro-PrP isoform continues to possess the GPI anchor peptide signal sequence which is able to provide a binding motif for filamin A, which participates in modulating cancer cell proliferation and migration in colorectal cancer cells and the expression of BRCA1 in breast cancer [48,50,51]. However, the involvement of PrP C itself or its various forms in different vital pathways that control cancer cell migration, tumour invasion and metastasis, and immune responses during cancer development still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%